The Quality Control Analysis of Hard Solder Assembly (HSA) of Key Flutes Using the Six Sigma DMAIC Method (Case Study: PT. Yamaha Musical Products Indonesia) - Khoirul Iqbal; Trio Yonathan Teja Kusuma Yonathan (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2026)
Quality control is a critical aspect of manufacturing industries to ensure product consistency and minimize defect, and propose quality improvement actions using rates. PT. Yamaha Musical Products Indonesia a manufacturer of wind musical instruments, still encounters quality issues in the Hard Soldering Assembly (HSA) Key-Flute product that affect production efficiency. This study aims to identify dominant defect types, evaluate process performancethe Six Sigma DMAIC (Define, Measure, Analyze, Improve, and Control) approach. The study utilizes production and defect data collected during June 2025. The measurement stage shows an average Defect Per Million Opportunities (DPMO) value of 2,738.42 with a Sigma Level of 4.29, indicating that the process performance is not yet optimal. Pareto analysis reveals that the Ro Tare defect contributes more than 80% of total defects. Root cause analysis using a fishbone diagram identifies human, machine, method, and material factors as the main causes. Proposed improvements include operator retraining, work standardization, machine maintenance, material quality control, and manpower optimization to enhance process stability